2011
DOI: 10.1111/j.1464-5491.2011.03367.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of a specialized approach for patients with diabetes, critical ischaemia and foot ulcers not previously considered for proactive management

Abstract: Management of patients with diabetes, foot ulcers and critical limb ischaemia by means of a proactive approach including endovascular procedures in specialized settings provides a high rate of limb salvage. This may result in lowering the number of lower limb amputations in our community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…1 The endovascular approach, mainly involving angioplasty of below-the-knee lesions, is associated with good rates of limb salvage with low morbidity and mortality. 6 Despite these good results in complex lesions, 4,6 scarce information existed regarding its usefulness in patients with TAO and foot ulcers until now. Angioplasty and thrombolysis were reported in one case of acute ischaemia, 7 and other authors reported a successful procedure in a 36-year-old man with untreatable rest pain in an article dealing with below-the-knee angioplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The endovascular approach, mainly involving angioplasty of below-the-knee lesions, is associated with good rates of limb salvage with low morbidity and mortality. 6 Despite these good results in complex lesions, 4,6 scarce information existed regarding its usefulness in patients with TAO and foot ulcers until now. Angioplasty and thrombolysis were reported in one case of acute ischaemia, 7 and other authors reported a successful procedure in a 36-year-old man with untreatable rest pain in an article dealing with below-the-knee angioplasty.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that a series including 20 cases treated by the endovascular approach resulted in a 100% of limb salvage rate. 3 Based on our experience treating difficult cases of critical ischemia in patients with diabetes involving below-the-knee lesions by endovascular approach, 4,5 and encouraged by the experience from other authors, we decided to give a chance of limb salvage to a patient with Buerger’s disease, critical ischemia, and big toe ulcer who had been scheduled for a big toe amputation by another team. The patient gave informed, written consent to be operated on and photographed and for his case report to be published anonymously.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, concomitant diabetes mellitus, wound infection, extensive wound size, and other serious comorbidities could have a substantial negative effect on clinical outcomes. 11,12,19 In the clinical setting, the quality of wound management can also influence wound healing, and patientphysician preferences can affect the decision for major amputation. Furthermore, although the toes are frequent sites of tissue loss, some investigators consider them to be in the angiosome of the PTA, 9,20 whereas others contend that the dorsal aspect of the toes belongs to the angiosome of the ATA and the plantar aspect of the toes belongs to the angiosome of the PTA.…”
Section: Discussionmentioning
confidence: 99%
“…51 Even though tissue loss is complicated by diabetes mellitus and infection, an individualized approach with specialized physicians (plastic surgeon, dermatologist or orthopedic surgeon etc) and nurses can enhance the possibility of clinical success (Figures 6A,B). Diabetes mellitus can change the nature of infrapopliteal Note non-healing ulcer on the 2nd toe (arrow).…”
Section: Multidisciplinary Approach For Ischemic Wound With Diabetes mentioning
confidence: 99%